(3bQI GdYjf HeG LGA eSdSdkG aj GdMOjKjf Hjhe YGThQGAs
(3ChdgG (B:s
(3gPG LRA PcQJ ajg eG hQO ef GdCMGOjK ai jhe YGThQGA GdJi ChQOgG GdTjNGf hGdfSGFi hGdHjgbi s
(3BNQgG (B:s
(3bGd cGf QShd Gddg Udi Gddg Ydjg hSde jbhd Ef CaVd GdUdGI HYO GdeaQhVI GdUdGI ai Lha Gddjd hCaVd GdUjGe HYO QeVGf TgQ Gddg GdPi JOYhfg GdeMQe JeJ hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs